Critical evaluation of a badminton-specific endurance test - Fuchs, M.; Faude, O.; Wegmann, M.; Meyer, T. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To overcome the limitations of traditional 1-dimensional fitness tests in analyzing physiological properties of badminton players, a badminton-specific endurance test (BST) was created. This study aimed at analyzing the influence of various fitness dimensions on BST performance. Methods: 18 internationally competing male German badminton players (22.4 ± 3.2 y, 79.2 ± 7.7 kg, 1.84 ± 0.06 m, world-ranking position [WRP] 21-501) completed a straight-sprint test, a change-of-direction speed test, various jump tests (countermovement jump, drop jump, standing long jump), a multistage running test (MST), and the BST. During this on-court field test players have to respond to a computerized sign indicating direction and speed of badminton-specific movements by moving into the corresponding corners. Results: Significant correlations were found between performance in MST and BST (individual anaerobic threshold [IAT], r = .63, P = .005; maximum velocity [Vmax], r = .60, P = .009). A negative correlation (r = -.59, P = .014) was observed between IAT in BST and drop-jump contact time. No further associations between performance indices could be detected. Apart from a small portion explained by MST results (IAT, R2 = .40; Vmax, R2 = .36), the majority of BST performance cannot be explained by the determined physiological correlates. Moreover, it was impossible to predict the WRP of a player on the basis of BST results (r = -.15, P = .55). Conclusions: Neither discipline-specific performance nor basic physiological properties were appropriately reflected by a BST in elite badminton players. This does not substantiate its validity for regular use as a testing tool. However, it may be useful for monitoring on-court training sessions.